Enhancing biomineralization process efficiency with trained bacterial strains: A technical perspective - Chang Zhao; Vahab Toufigh; Jinxuan Zhang; Yi Liu; Wenjun Fan; Xiang He; Baofeng Cao; Yang Xiao (Biogeotechnics)
Microorganisms have been essential in the natural world for millions of years, contributing significantly to environmental interaction. It has been disoverd that some bacteria are potential in geotechnical and environmental engineering due to their outstanding ability of biomineralization. Therefore, how to train bacteria as special and professional “workers” for biomineralization is increasingly a key topic in related research fields. This article briefly introduces the methods that are commonly utilized to improve the environmental adaptability and mineralization efficiency of bacteria, including microbial domestication, microbial mutation breeding, microbial targeted screening, and bio-stimulation, which make great implications to advance the field of biomineralization.